The Prevalence of Schistosoma haematobium and Its Impact on the Hematological Profile of Children Living in Northern Madagascar - Wanesa Wilczyńska; Daniel Kasprowicz; Dariusz Świetlik; Krzysztof Korzeniewski (Pathogens)
Schistosomiasis is a parasitic disease that is considered a major threat to public health in Madagascar. The condition is endemic in more than 90% of the country’s districts. It is estimated that as much as 52% of the country’s general population is infected with Schistosoma spp. trematodes. The aim of the present study was to assess the prevalence values of Schistosoma haematobium infections in a population of children living in northern Madagascar and to determine the impact of trematode infections on the hematological profiles of the children included in the study. This screening study was conducted in 2024, and it involved a group of 170 children aged 0–17 years. The participants were required to provide urine samples for microscopic and molecular examination. The urine samples were preserved on Whatman 903 protein sever cards using the dried urine spot (DUS) sampling technique and then were transported from Madagascar to a molecular laboratory in Poland, where the samples were tested for the presence of S. haematobium. The present study found that the incidence of S. haematobium infections in the study group consisting of 170 children was as high as 67.6%. The authors observed a reduction in mean hemoglobin (Hb) and mean corpuscular hemoglobin concentration (MCHC) values in the infected children. In spite of continuous efforts to prevent the transmission of schistosomiasis in endemic countries (WHO-recommended mass drug administration campaigns), the incidence of S. haematobium infections was found to be exceptionally high among the study participants. S. haematobium infections present with a characteristic hematological picture showing signs of increased immune response and anemia. The DUS technique has been successfully used for the molecular diagnosis of S. haematobium. This method opens up possibilities for more effective and less expensive sample collection.